Large Hail in Poland in 2012 - Taszarek, Mateusz; Suwała, Katarzyna (Quaestiones Geographicae, 2015)
This report analyses significant hailstorms that occurred in Poland during 2012. The number of reports, derived from the European Severe Weather Database with the hail diameter over or equal 2 cm, were analyzed with respect to their frequency in individual months, time of the day, intensity and spatial distribution. Analyzed cases were divided for hail with diameter less than 4 cm and greater or equal 4 cm. Accompanying conditions were examined by synoptic analysis charts derived from Deutscher Wetterdienst. The total number of 121 large hail cases gave 26 days with this phenomenon. The period of their occurrence extended from April to August reaching peak in July. Above 60% of all events were reported between 1500 and 1800 UTC. Most of them were associated with cold front and squall line features, usually with the south-western warm and moist air mass influx.